2018
DOI: 10.1136/gutjnl-2018-316001
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pharmacological therapies for the treatment of opioid-induced constipation: systematic review and network meta-analysis

Abstract: In network meta-analysis, naloxone and naldemedine appear to be the most efficacious treatments for OIC. Naloxone was the safest of these agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 63 publications
2
57
0
1
Order By: Relevance
“…Expert Group of the European Society of Medical Oncology and Polish Association for Palliative Medicine recommend a consideration of PAMORA in the management of OIC [40,41]. Current data from clinical studies and systematic reviews indicate that naldemedine is an effective and generally well-tolerated treatment option for OIC in patients with cancer pain or chronic non-cancer pain, with the convenience of once-daily oral dosing [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Expert Group of the European Society of Medical Oncology and Polish Association for Palliative Medicine recommend a consideration of PAMORA in the management of OIC [40,41]. Current data from clinical studies and systematic reviews indicate that naldemedine is an effective and generally well-tolerated treatment option for OIC in patients with cancer pain or chronic non-cancer pain, with the convenience of once-daily oral dosing [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…nalexagol, naldemedine, methylnaltrexone) alleviate the symptoms of OIC by blocking the mu-opioid receptors within the GI tract, but as they do not cross the blood-brain barrier they do not diminish the central analgesic effect of opioids nor induce withdrawal symptoms. A systematic review and network meta-analysis of randomized controlled trials has found PAMORAs to be superior to placebo for the treatment of OIC [37]. A recent European expert consensus statement on OIC advises PAMORAs to be prescribed if standard laxatives have failed, which will be the case in up to 50% of cases [36].…”
Section: Peripherally Acting Mu-opioid Receptor Antagonists (Pamoras)mentioning
confidence: 99%
“…There have been many studies aiming to explore methods to facilitate postoperative GI recovery, including the following: 1) multimodal analgesia to reduce the use of opioids, e.g., other analgesic methods and non-steroidal anti-in ammatory drugs (NSAIDs) [20,21]. 2) laparoscopic surgery [22]; 3) goal-directed uid therapy [22]; 4) early enteral nutrition [23]; 5) gum chewing [24]; 6) opioid receptor antagonist [25]; 7) traditional Chinese medicine [26]. All of these methods play a limited role.…”
Section: Incidence and Degree Of Postoperative Abdominal Bloatingmentioning
confidence: 99%